Identification and distribution of microsymbionts associated with soybean nodulation in Mozambican soils - Gyogluu, C.; Jaiswal, S.K.; Boahen, S.; Dakora, F.D. (Elsevier, 2018)
Indigenous soybean rhizobial strains were isolated from root nodules sampled from farmers’ fields in Mozambique to determine their identity, distribution and symbiotic relationships. Plant infection assays revealed variable nodulation and symbiotic effectiveness among the 43 bacterial isolates tested. Strains from Ruace generally promoted greater whole-plant growth than the others. 16S rRNA-RFLP analysis of genomic DNA extracted from the rhizobial isolates produced different banding patterns, a clear indication of high bacterial diversity. However, the multilocus sequence analysis (MLSA) data showed alignment of the isolates with B. elkanii species. The 16S rRNA sequences of representative soybean isolates selected from each 16S rRNA-RFLP cluster showed their relatedness to B. elkanii, as well as to other Bradyrhizobium species. But a concatenated phylogeny of two housekeeping genes (glnII and gyrB) identified the soybean nodulating isolates as Bradyrhizobium, with very close relatedness to B. elkanii. The nifH and nodC sequences also showed that the majority of the test soybean isolates were closely related to B. elkanii, albeit the inconsistency with some isolates. Taken together, these findings suggest that the B. elkanii group are the preferred dominant microsymbiont of soybean grown in Mozambican soils. Furthermore, the distribution of soybean rhizobia in the agricultural soils of Mozambique was found to be markedly influenced by soil pH, followed by the concentrations of plant-available P and Mn. This study suggested that the identified isolates TUTMJM5, TUTMIITA5A and TUTLBC2B can be used as inoculants for increased soybean production in Mozambique.